Kehadiran Amerika Serikat di Kasus Sudan Selatan pada tahun 2011-2015: Bantuan Kemanusiaan atau Kepentingan Strategis - Muhammad Fajar Febrianto; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2019)
The problems that occurred in South Sudan in 2011-2015 caused a crisis in South Sudan. the presence of the United States to providing humanitarian assistance in South Sudan has an interest it self. This thesis seeks to reveal the interests of the United States in terms of incorporating strategic interests in South Sudan. The theory of Neorealism, the Concept of National Interest and the Concept of Balance of Power in International Relations are used to explain facts and phenomena and as a basis in building scientific arguments in answering research questions. Built arguments are sourced from sources in the form of reports and other library sources that are processed qualitatively based on existing theories so as to produce explanatory arguments as research answer. Based on data processing using existing theories, the United States in providing assistance to South Sudan is not only limited to providing strategic interests but also related to expanding the influence of the United States in South Sudan. With China in South Sudan providing a security threat to the United States, the United States is also present in order to containtment China's influence.